Recession and Recovery in the United Kingdom in the 1990'+L927s : A Vector Autoregression Approach - Catao, Luis (IMF Working Papers; Working Paper, 1995)
This paper uses a vector autoregression (VAR) approach to identify the causes of the 1990-92 recession in the UK. The VAR approach is shown to be particularly pertinent for quantifying the relative magnitude of the different demand shocks, and in decomposing them into monetary and expectational factors. The main finding is that the recent recession was precipitated primarily by shocks to consumption, and that monetary factors explain just part of this contraction. The VAR model also offers interesting insights about the long duration of the recession and the nature of the recovery that is currently underway.